The Negative Interactive Effects of Nostalgia and Loneliness on Affect in Daily Life - Newman, David B.; Sachs, Matthew E. (Frontiers in Psychology, 2020)
Research has suggested that nostalgia is a mixed, albeit predominantly positive emotion. One proposed function of nostalgia is to attenuate the negative consequences of loneliness. This restorative effect of nostalgia, however, has been demonstrated with cross sectional and experimental methods that lack ecological validity. In studies that have measured nostalgia in daily life, however, nostalgia has been negatively related to well-being. We propose an alternative theory that posits that the effect of nostalgia on well-being depends on the event or experience that elicits nostalgia. We tested this theory by measuring daily states of nostalgia, loneliness, and affect across five daily diary studies (N = 504; 6,004 daily reports) that lasted for fourteen days. Using multilevel modeling, we found that nostalgia and loneliness were negatively related to positive affect and positively related to negative affect. The negative effects of nostalgia on affective well-being were significantly stronger on days when people felt more lonely as opposed to less lonely. Viewed alternatively, the negative effects of loneliness on affective well-being were stronger on days when people felt more vs. less nostalgic. Thus, in contrast to experimental findings, nostalgia did not attenuate, but rather exaggerated the negative effects of loneliness on affective well-being. These findings support a theoretical account that proposes that the effect of nostalgia on well-being depends on the natural context in which nostalgia is elicited.